Aggressive behaviour of Hodgkin's-like lymphoma in a domestic ferret - Kim, Hyo-Sung; Kim, Han-Jun; Hwang, Hyun-Jeong; Oh, Sukhun; Do, Sun Hee (Veterinarni medicina, 2021)
A 3-year-old castrated male ferret was suspected to have lymphoma based on a markedly enlarged mesenteric lymph node. Hodgkin's-like lymphoma (HLL) was suspected because numerous Reed-Sternberg-like cells were observed in the fine-needle aspiration biopsy of the mesenteric lymph node. In the post-mortem histopathology, neoplastic cells were invasively proliferated not only in the mesenteric lymph nodes, but also in the liver and spleen. Immunohistochemically, most neoplastic cells were positive for vimentin and BLA-36, weakly positive for CD20, and negative for Pax5, CD79a, CD3, CD45, and Iba-1, demonstrating similarity to human Hodgkin's lymphoma (HL). In addition, a prominent programmed cell death protein 1 (PD-1) expression was observed at the sites showing malignant tumour proliferation. HLL in non-human beings can be morphologically and immunophenotypically similar to human HL, but the prognosis and clinical outcome may differ. This is the first study analysing the PD-1 expression in a ferret, suggesting that PD-1 can be a novel diagnostic and prognostic factor in a similar manner to humans.
Keywords: immunohistochemistry; programmed cell death protein 1; histopathology; cytology; Reed-Sternberg cell